Peran Perbankan Syariah Dalam Pengembangan Eduwisata Di Desa Morkepek Kabupaten Bangkalan - Sipul, Sipul; Burhan Noor Hasan, Dony (MADINAH, 2022)
Madura Island is one of the islands which has four regencies including Bangkalan, Sampang, Pamekasan, and Sumenep regencies. One of the districts that has attractive tourism potential is located in Bangkalan which is the closest district to the city of Surabaya so that many tourists come. The number of tours in Bangkalan district is 21 which consists of religious tourism objects, history, natural education. One of the educational tours in Bangkalan is a tree house located in Morkepek Village which can be used as an educational tour because there are medicinal plants in the tour that we can learn how to plant and care for. The research method used by the researcher is a qualitative research method in which the process of searching for data is through observation and thorough techniques regarding the problem of the existence of tourism in Markopek Village, Bangkalan. This study aims to analyze the role of Islamic Banking in developing tourism through existing resources, namely mango trees and what contracts will be used in the process